Understanding the genetic structure of symplocos laurina wall. populations using nuclear gene markers - Banu, Sofia; Bhagwat, Rasika M.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, V. S. (Genetica, 2010)
To characterize the genetic diversity of present populations of Symplocos laurina, which grow in the montane forests in India, we analyzed the DNA sequences of a nuclear gene. Using the 881 bp sequence of cytosolic Glyceraldehyde-3-phosphate dehydrogenase gene, we detected 24 haplotypes among 195 individuals sampled from 14 populations. Two dominant haplotypes were distributed over the entire range of this species in India and several private haplotypes were found. Low genetic diversity within population, high differentiation, number of population specific haplotypes and deviation from neutral evolution characterized the present populations of S. laurina. An analysis of molecular variance indicated the presence of geographic structure within the haplotype distribution. The occurrence of S. laurina preglaciation in India is the most parsimonious explanation for the current geographic structure observed. The populations are presumably ancient and might have spread across its extant distribution range in India through a recent range expansion event.
Keywords: GapC; Genetic diversity; Glaciation; Refugium